In vitro and in vivo biocompatibility of Mg–Zn–Ca alloy operative clip - Ding, Pengfei (Bioact Mater, 2019)
At present, titanium (Ti) and its alloys are most commonly use in hemostasis clip clinical applications. However, the Ti Clip cannot be absorbed in human body and produce artifacts on computed tomography (CT), and induce clinically relevant hypersensitivity in patients. In order to overcome the drawbacks of the non-degradable Ti clips, an Mg–Zn–Ca alloy operative clip was fabricated by combining hot extrusion and blanking processing. In vitro and in vivo biocompatibility of Mg–Zn–Ca alloy operative clip were evaluated by L-929 Cells and SD rat model respectively. It was found that Mg–Zn–Ca alloy exhibited non-cytotoxic to L929 cells. In vivo implantation showed that the newly designed Mg–Zn–Ca clip can successfully ligated carotid artery and no blood leakage occurred post-surgery. During the period of the clip degradation, a small amount of H(2) gas formation and no tissue inflammation around the clips were observed. The degradation rate of the clip near the heart ligated the arteries faster than that of clip far away the heart due do the effect of arterial blood. Histological analysis and various blood biochemical parameters in rat serum samples collected at different times after clip implantation showed no tissue inflammation around the clips.